Study on Seroprevalence and Associated Factors of Bovine Brucellosis in Selected Districts of Afar National Regional State, Afar, Ethiopia - Wossene Negash; Teshager Dubie (Veterinary Medicine International)
Bovine brucellosis is among the top five diseases primarily threatening both public health and livestock economy. Available data are limited to central and highland areas of the country leaving documented literature on the disease in cattle to be found hardly in pastoral and agropastoral regions of the country. As a result, the magnitude and extent of the disease remained to be investigated. A cross-sectional study design was conducted on local Afar cattle aged six months and above from February 2017 to January 2019 in selected districts of Afar region. Technically, study districts and kebeles were selected purposively whereas simple random sampling technique was applied to select cattle owners and individual animals for sample collection. An average of 8 ml whole blood was drawn of jugular vein into plain vacutainer tube using sterile needle. Using Thrusfield formula, a total of 420 blood samples were collected. The sera were tested by RBPT and CFT tests for detection of Brucella antibodies. Data were analyzed using Stata v14.0. Of the 420 sera tested by RBPT, 50 were positive for Brucella antibodies providing an overall animal level prevalence of 11.9% and those RBPT positive sera were further retested by specific and sensitive confirmatory CFT test and 24 of the retested samples had come positive for the disease providing an overall individual animal seroprevalence of 5.7% over the three districts. Of the 3 associated factors (sex, age, and district) considered, only sex had significantly associated (P<0.05:0.036) with the disease. To estimate the strength of sex impact, odds ratio was generated using bivariate and multivariate logistic regression analyses with 95% CI and P<0.05 providing OR of 2.484 (1.061–5.815) and 2.514 (1.041–6.07), respectively. Hence, the computations revealed that male cattle were 2.484 and 2.514 times more likely at higher risk for the disease as compared to their female counterparts.